PENDEKATAN EDUKATIF PADA IBU TENTANG PERAWATAN PAYUDARA PADA MASA NIFAS - Epi Satria; Novi Maya Sari; Afrah Diba Faisal (COVIT (Community Service of Health), 2022)
During the puerperium breast care is a very important action to care for the breast especially to facilitate the release of milk. Breast care is very important during pregnancy until breastfeeding. This is because the breast is the only producer of breast milk which is the staple food for newborns, so it must be done as early as possible. The purpose of this activity is so that all postpartum women at the Padang Pasir Health Center know about virgin breasts during the postpartum period. So that the production of breast milk in postpartum mothers smoothly Keywords: Knowledge, Breast Care During Puerperal Period